Report of the administration of the British-United States : Zone of the free territory of Trieste : 1 october to 31 december 1949 : Report number 9 - Airey, T.S. (Trieste, 1950)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: territoriale kwesties; Trieste